Abigaill Abbott deposition - Abbott, Abigaill
Signed testimony (Cork, Ireland; 1709 November 2) of Abbott publicly declaring her sins.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Quakers -- Ireland